PLANNING AND DESIGNING STANDARD OF RURAL ROAD CONSTRUCTION - AN EXPLORATORY STUDY: A CASE OF LUSAKA PROVINCE IN ZAMBIA - Erastus MWANAUMO; Ephraim SAKALA (Journal of Construction Project Management and Innovation)
The state of rural roads in Zambia is very poor and in a deplorable condition. Drainages are missing, or where they exist, they are narrow, inadequate and not constructed correctly. Bridges are missing, old, inadequate or wrongly constructed and usually very poorly maintained. In most roads, the shoulders are not stable. From reviewed literature, several gaps in the planning, design, specifications, funding and general roads management in Zambia were identified as being the root causes of poor-quality rural roads. An in-depth literature review was carried out as secondary sources using journals, rural road construction handbook, peer reviewed articles, dissertations and the internet. In-depth interviews were further carried out with the staff at Ministry of Finance, Road Development Agency (RDA), National Road Fund Agency (NRFA), National Council for Construction (NCC), Rural Road Unit and also the Royal Highnesses and their subjects in Chongwe and Lusaka North areas. The results show that the planning is adequate but the problem lies with the planning personnel who are not adequately trained to undertake the tasks. Designs and specifications needed to consider the alignment requirements, technical performance, pavement solutions, material requirements and structures that are specific to an area. Results indicate that planners use a one-size fits all approach kind of designing resulting in the quality deficiency in some areas. The research assist government in developing and disseminating improved policies that assists in better planning, constructing and maintenance of rural roads. It introduces mitigatory actions and recommendations which the government can utilize in coming up with sustainable and reliable quality rural roads